La Gamificación como método didáctico en la enseñanza de la Historia del bloque: 5 La civilización Romana en primero BGU. - Caguana Ñamiña, Katherine Jimena (2025)
This research examines the implementation of gamification as a teaching strategy in teaching History for first-year high school students in Ecuador. This qualitative study provides a systematic review of academic sources and the analysis of three representative cases. The results indicate that gamification fosters student engagement, with most cases reporting a notable increase in motivation and improving academic performance, particularly in content retention. These improvements were primarily observed in activities such as historical simulations and role-playing games, which promote the development of critical thinking. However, its effectiveness depends on key factors: 1) teacher training—with studies recommending minimum specialized training; 2) adaptation to the local context—such as the use of offline resources in rural areas; and 3) well-structured curricular integration. The comparative case analysis revealed that projects such as "Independence Escape Room" (Quito) enhanced historical understanding through gamified primary documents. At the same time, the "Riobamba AR" application demonstrated high effectiveness in learning local History, although technological limitations were identified for some students. These experiences, along with international cases such as "Playing History 2" (Denmark), underscore the importance of striking a balance between pedagogical innovation and institutional feasibility. As a main contribution, we propose a gamified model based on five adaptable strategies: 1) role-playing games for complex historical processes, 2) simulations with physical and digital materials, 3) offline platforms, 4) immediate feedback mechanisms, and 5) competency-based rubrics. The conclusions underscore that gamification transforms History teaching by making it more interactive but requires teacher training policies and investment in infrastructure for its consolidation. This study presents the first contextualized methodological framework for Ecuador, offering practical guidelines for its application in thematic units, such as "Roman Civilization," with special attention to the country's educational diversity. Keywords: Gamification, History Teaching, Ecuadorian Education, Student Motivation, Student Engagement, Problem-solving, Collaboration, Educational Innovation.